Babymouse. [10], The musical - Holm, Jennifer L.; Holm, Matthew (New York : Random House, 2009)
As tryouts for the school musical begin, Babymouse takes the starring role in several imaginary Broadway productions, which also feature her debonair new classmate, Henry the hedgehog.
2.4
3-6.
3-6
Keywords: Animals -- Comic books, strips, etc -- Juvenile fiction; Babymouse (Fictitious character) -- Comic books, strips, etc -- Juvenile fiction; Imagination -- Comic books, strips, etc -- Juvenile fiction; Mice -- Comic books, strips, etc -- Juvenile fiction; Musicals -- Comic books, strips, etc -- Juvenile fiction; Theater -- Comic books, strips, etc -- Juvenile fiction; Animals -- Fiction; Babymouse (Fictitious character) -- Fiction; Cartoons and comics; Imagination -- Fiction; Mice -- Fiction; Musicals -- Fiction; Theater -- Fiction; Animals -- Comic books, strips, etc -- Fiction; Babymouse (Fictional character) -- Comic books, strips, etc -- Fiction; Comic books, strips, etc; Graphic novels; Imagination -- Comic books, strips, etc -- Fiction; Mice -- Comic books, strips, etc -- Fiction; Musicals -- Comic books, strips, etc -- Fiction; Theater -- Comic books, strips, etc -- Fiction; Graphic novels